2019
DOI: 10.3747/co.26.5005
|View full text |Cite
|
Sign up to set email alerts
|

Combining Prostate Cancer Radiotherapy with Therapies Targeting the Androgen Receptor Axis

Abstract: Background Prostate cancer (pca) is the most common non-dermatologic cancer and the 3rd leading cause of male cancer mortality in Canada. In patients with high-risk localized or recurrent pca, management typically includes the combination of long-term androgen deprivation therapy (adt) and radiotherapy (rt). New androgen-receptor-axis targeted therapies (arats), which await validation, offer an option to intensify therapy.Methods In this narrative review, we report the relevant history that has supported combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…We and some groups have demonstrated that AR expression and activity are upregulated following IR in PCa models and AR can activate DDR pathways [4,5,10,39,40] in PCa, providing rationale for concurrent ADT + RT therapy [6,41] as being better than RT therapy alone. These preclinical studies also have led to testing combinations of RT with next generation hormonal agents such as abiraterone, Enz, apalutamide and AR degradation enhancer, ASC-J9 [40,[42][43][44][45]. However, despite use of combined ADT and RT, the recurrence rate is up to 50% in high-risk PCa patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…We and some groups have demonstrated that AR expression and activity are upregulated following IR in PCa models and AR can activate DDR pathways [4,5,10,39,40] in PCa, providing rationale for concurrent ADT + RT therapy [6,41] as being better than RT therapy alone. These preclinical studies also have led to testing combinations of RT with next generation hormonal agents such as abiraterone, Enz, apalutamide and AR degradation enhancer, ASC-J9 [40,[42][43][44][45]. However, despite use of combined ADT and RT, the recurrence rate is up to 50% in high-risk PCa patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support using a lead-in design for nonhormonal novel agents combined with RT and ADT, especially when an early phase combination is administered with curative intent. Moreover, androgen–receptor-axis targeted drugs combined with RT and ADT are under investigation, 19 and the results are highly anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…We and some groups have demonstrated that AR expression and activity are durably upregulated following IR in PCa models and AR can activate DDR pathways (4,5,10,39,40) in PCa, providing rationale for concurrent ADT + RT therapy (6, 41) is better than RT therapy alone. These preclinical studies also have led to testing combinations of RT with second-generation antiandrogens such as abiraterone, enzalutamide, apalutamide and AR degradation enhancer, ASC-J9 (40,(42)(43)(44)(45). However, despite use of combined ADT and RT, the recurrence rate is up to 50% of high-risk PCa patients (6).…”
Section: Discussionmentioning
confidence: 99%